L’intérêt général au crible de l’intérêt commun - Pierre Crétois (Astérion)
The general interest (by opposition to the common interest) presents itself as a position of overhang, taking the point of view of society and the requirements of rationalization supposed to structure it. We propose to examine three different options concerning the nature and the determination of this interest. We follow a chronological approach which, in fact, refers to essential conceptual distinctions. Lemercier de La Rivière’s approach shows general interest as a mere epiphenomenon of the interest of the members of society who are all seeking to see their individual gains maximized. The approach of Saint-Simon overturned it because, for him, the rights of individuals depend entirely on their social function in the industrial system in such a way that the only common interest of individuals is their interest as member of the industrial society. The general interest assumed by the State expresses the general requirements of industry, i.e. the production and optimum distribution of resources throughout the whole body of society. Finally, Leon Bourgeois' approach allows to articulate a thesis based on the rights and protection of individuals with a thesis based on the promotion of social interests irreducible to individual interests. The general interest incarnated by the State aims to reinstate the individual in the requirements and the civic obligations in particular by duties like that of paying the tax.